VISUALISASI DAN UJI COBA METODE PERAWATAN LANTAI KERAMIK GUNA PEMBELAJARAN VIRTUAL - Santosa, Stefanus; Suwarto, Suwarto; Suroso, Suroso; Setiyono, Karnawan Joko; Setyaningsih, Desi; Ilala, Oze Dora (Politeknik Negeri Semarang, 2023)
The Architecture, Engineering, Construction, and Operations (AECO) industry has shown high interest in the use of Building Information Modeling (BIM) for Facility Maintenance Management (FMM). The opportunity to use BIM for the operational activities of building facilities is very large, but the use of BIM in FM is still far behind compared to the implementation of BIM at the design and construction stages. This research is intended to test the tile floor maintenance method and create visualizations in animative form and apply them in virtual learning with evaluation based on the Technology Acceptance Model (TAM). The results of the student t-test statistical test showed that there was a very significant effect of the Ceramic Floor Care Method Learning Media on increasing user knowledge in 5 aspects (learning objectives, knowledge, materials, service quality, and appearance). The test results by media experts on the aspects of language, display, and service quality obtained the